Measuring the effect of Asian financial crisis on the comparative advantage of the food processing industry - Ismail, Mohd Mansor; Radam, Alias (Faculty of Economics and Management, Universiti Putra Malaysia, 2010)
This paper investigates the effect of the 1997 Asian financial crisis on the levels of competition for various productions of food products. The study is undertaken using the concept of comparative advantage. In the context of competitiveness of the Malaysian food processing industry the evaluation of comparative advantage has been undertaken with special reference to the prior implementation of the scheduled liberalization of trade preferences under the WTO and AFTA in 2010. In order to penetrate a wider range of foreign markets, Malaysian food processors have to identify food sectors that are internationally competitive and could withstand internal and external shocks. The Malaysian competitiveness level was determined using the Domestic Resource Cost (DRC) and Social Cost Benefit (SCB) indicators. Twenty food sectors were assessed using the Malaysian food production and trade data from 2000 to 2005. The results indicate that in the post crisis period, Malaysia enjoys an above average level of comparative advantage in the production of edible oil and fat from vegetables and animals, fish and, glucose and maltose. As expected, Malaysia has a comparative disadvantage in the production of paddy.